Appendicular Biopsy in Total Colonic Aganglionosis: A Histologically Challenging and Inadvisable Practice. (July 2017) - Mohanty, Suravi; Kini, Usha; Das, Kanishka; Puttegowda, Divya; Yadav, Lokendra; Babu, Manjally Kunjipapu; Mahadevappa, Kiran; Kumar, Prasanna; Mahadevaiah, Shubha Attibele; Deb, Mainak
Background: The reliability of intraoperative evaluation of ganglion cells in the appendix as a guide to a diagnosis of total colonic aganglionosis is unclear. Objective: To evaluate the diagnostic utility of appendicular innervation in colonic Hirschsprung disease (HD) and TCA. Methods: Prospective, systematic study of ganglion cells and the neural plexii in appendices from cases (HD and TCA) and age matched controls with frozen and paraffin sections, rapid acetylcholinesterase (AChE) and immunohistochemistry. Results: A total of 48 appendices (28 controls, 20 cases; 19 frozen) were evaluated. Of these 48, 30 were neonates. Ganglion cell clusters were smaller in controls (28) and HD (6) than those in the rectum, distorted at places and mimicked lymphocytes and endothelial cells, especially in neonates. Complete study of 13 appendices in TCA showed absence of ganglion cells, hypertrophic nerves, AChE activity, and calretinin staining. In 2/13 TCA, an erroneous frozen section identification of ganglia was later corrected based on AChE histochemistry and a panel of IHC stains. Ileal biopsies guided the placement of a ganglionic ileostomy in all. One case each of skip segment aganglionosis in a TCA and variable hypoganglionosis in long segment colonic HD is reported. Conclusion: Intraoperative characterization of appendicular innervation as a guide to the diagnosis of TCA is unreliable, in part because of the possibility of skip segment disease/variable hypoganglionosis. We propose terminal ileal biopsies for diagnosis and leveling of aganglionosis. AChE on frozen/calretinin on paraffin tissue is the best approach to avoid diagnostic errors.